PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN DARING OLEH DOSEN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Andi Mappincara; Andi Nurochmah; Syamsurijal Basri (JOEL: Journal of Educational and Language Research, 2022)
This study examines student percepstions of the implementation of l=online learning by lectures of the Faculty of Education in the even smester of 2021-2022. The purpose of this study was to describe student perseceptions of the implementation of online learning at the Fakulty Of Education Makassar State University. This research was carried out at the Faculty of Education Makassar State University. This research and the data sources in thi study were all students of the Faculty of Edecation, batch 2020, totaling 5190 people for seven majors. However, the researchers took a simple of 500 students representing each departement. The results of this study proved that student’s perceptions of line learning carried out by FIP Makassar State Universitas lecturers were satisficatory and very satisfying both from the lesson plants prepared bay the lecturers, as well as implementation of learning and evaluation showed effektif results so that students felt well served. On the Syam system Ok